SURFACE RUNOFF AND SOIL ORGANIC MATTER AVAILABILITY IN BAMBOO-BASED AGROFORESTRY IN LOMBOK TIMUR DISTRICT - Handoko, Cecep (Secretariat of Forestry Research and Development Agency, 2012)
Bamboo-based agroforestry is suitable for soils which are poor in nutrient. The characteristics of bamboo and the rapid closure of its canopy improve soil cover, soil nutrient availability and soil moisture content, and prevent erosion by reducing surface runoff. The research was aimed at determining the factors that influenced surface runoff and the availability of soil organic matter (SOM) in the bamboo-based agroforestry in East Lombok. Research was done from March 2010 to March 2011 in Lenek Daya village, Aikmel sub-district, East Lombok district. The research plots were located on slopes of 0-15o, 30-45o, and 45-65o; with bamboo canopy closures of 0-25%, 25-50%, 50-75%, and over 75%. The research involving 12 plots, each in 4 x 12 m size. Measurements included surface runoff, bamboo canopy closure, weeds and bamboo leaves litter weight, rainfall depth and duration, dissolved sediment, and soil physical and chemical properties as well as SOM. Correlation and multiple linear regression tests were used in data analysis. The results of the regression tests showed a change in surface runoff which was influenced by changes in bamboo canopy closure, rain duration, rain intensity and soil sand fraction, each by -0.019, 0.418, 0.049 and -0.065 respectively. Rain duration was the highest influencing variable, whereas bamboo canopy closure significantly decreased surface runoff. Bamboo canopy closure had no correlation with the increase of SOM. But, the increase of SOM had correlation with the increase of soil cation exchange capacity (CEC). The positive impact of bamboo canopy closure on Regosol soil fertility in bamboo-based agroforestry land was determined by land management intensity which could increase the availability of SOM and decrease phosphorus element loss due to leaching of nutrient.